Função atrial esquerda em gatos saudáveis e gatos com cardiomiopatia: da ecocardiografia convencional ao speckle tracking bidimensional - Abreu, Claudine Botelho de (2021)
The establishment of two dimensional speckle tracking echocardiography (STE 2D) enabled the development of new parameters of atrial function, the strain and strain rate. These indices have been shown to be superior to conventional linear and volumetric echocardiographic variables. In cats, however, there is little information about the use of this technique in the assessment of left atrial function. Thus, the aim of this article was to determine reference intervals for left atrial strain and strain rate in the reservoir (StR, SRR), conduction (StCd, SRCd) and contraction (StCt, SRCt) phases in healthy cats and compare them to cats with cardiomyopathies. Seventh six healthy cats and seventeen cats with cardiomyopathies were evaluated. In 35 healthy animals it was possible to obtain strain and strain rate in the three phases (StR=36.5%; StCd=25.5%; StCt=10.9%; SRR=2.6/s; SRCd= 2.9/s; SRCt= 2/s). In all animals, it was possible to assess strain and strain rate of the reservoir, which were reduced in the cardiopathies ones (StR=26.2%; SRR=2.3/s; p=0.006; p=0.004). Both parameters showed good ability to distinguish the two groups, with cutoff values of 31.72% (sensitivity 70.6% and specificity 69.7%) for the StR and 2.48/s (sensitivity 70.6% and 67.1% specificity) for the SRR. There was a positive correlation of strain and strain rate with atrial ejection fraction and the hemodynamic variables E, E/A, E’, A’, E’/A’. In conclusion, STE 2D mainly the reservoir phase demonstrated to be feasible and can be a useful tool to assess the left atrial function in the feline species.